2022
DOI: 10.1111/bjd.20777
|View full text |Cite
|
Sign up to set email alerts
|

The critical need for patient-reported outcome measures to assess the severity and impact of systemic sclerosis

Abstract: assessing health-related quality of life in chronic pruritus. Br J Dermatol 2022; 186:86-95. 8 U.S. Food and Drug Administration. Patient-reported outcome measures: use in medical product development to support labeling claims. Available at: https://www.fda.gov/regulatory-information/searchfda-guidance-documents/patient-reported-outcome-measures-usemedical-product-development-support-labeling-claims (last accessed 24 August 2021). 9 Terwee CB, Prinsen CA, Chiarotto A et al. COSMIN methodology for assessing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Patient-reported outcome measures are widely used in clinical practice and trials to assess the impact and severity of disease. 25 Of interest, in this study, no association was seen between energy expenditure (activity) and patient-reported measures of function.…”
Section: Discussionmentioning
confidence: 55%
“…Patient-reported outcome measures are widely used in clinical practice and trials to assess the impact and severity of disease. 25 Of interest, in this study, no association was seen between energy expenditure (activity) and patient-reported measures of function.…”
Section: Discussionmentioning
confidence: 55%